Dissecting causal relationships between immune cells, blood metabolites, and aortic dissection: A mediation Mendelian randomization study - Ao Li; ZiAn Feng; ShiHao Fu; ZhenXiao Ma; HaiYang Zhang; ZhiWei Zhao (International Journal of Cardiology: Heart & Vasculature)
Background: There exists a robust correlation between the infiltration of immune cells and the pathogenesis of aortic dissection (AD). Moreover, blood metabolites serve as immunomodulatory agents within the organism, influencing the immune system’s response and potentially playing a role in the development of AD. Nevertheless, the intricate genetic causal nexus between specific immune cells, blood metabolites, and AD remains partially elucidated. Objectives: This study aims to elucidate the causal relationships between specific immune cell types and the risk of developing AD, mediated by blood metabolites, using Mendelian Randomization (MR) methods. Methods: We undertook a comprehensive investigation of 731 immune cell types through the analysis of published genome-wide association studies (GWAS). Our methodology hinged on the application of two-sample Mendelian randomization (MR) and mediator MR analyses, prioritizing blood metabolites as potential intermediary factors and AD as the principal outcome of interest. The primary statistical method employed was inverse variance-weighted estimation, complemented by a variety of sensitivity analyses to reinforce our conclusions. The entirety of our statistical analyses was executed on the R software platform. Results: Our analyses elucidated that three immune cell types exhibited a positive correlation with the incidence of AD, whereas two immune cell types were inversely associated with AD risk. Significantly, our mediation Mendelian randomization (MR) findings identified Benzoate as a pivotal mediator in the influence of CD19 on IgD − CD38br cells on AD, with a mediation proportion of 5.38 %. Additionally, N-acetylproline was determined to mediate the effect of CD24 on IgD- CD38- cells on AD, accounting for a mediation proportion of 13.70 %. Furthermore, Carnitine C5:1 was found to mediate the effect of CD28 on secreting T regulatory (Treg) cells on AD, with a mediation proportion of 17.80 %. Conclusions: These findings offer a nuanced understanding of the pathophysiological mechanisms underlying AD, thereby advancing the precision medicine paradigm in the clinical management of AD.Abbreviations: AD: aortic dissection; AA: aortic aneurysm; GWAS: genome-wide association study; MR: Mendelian randomization; TSMR: two-step Mendelian randomization; Treg: secreting T regulatory cell; VSMC: vascular smooth muscle cell; MMP: matrix metalloproteinase; ROS: reactive oxygen species; IV: instrumental variable; SNP: single-nucleotide polymorphism; IVW: inverse variance weighted; LDSC: linkage disequilibrium score regression; OR: odds ratio; CI: confidence interval; LD: linkage disequilibrium; AC: absolute cell; MFI: median fluorescence intensity; MP: morphological parameter; RC: relative cell; CLSA: Canadian Longitudinal Study of Aging; Lp(a): Lipoprotein a; OxPL: oxidised phospholipid; NMDAR: N-methyl-d-aspartate glutamate receptor; STROBE-MR: Strengthening the Reporting of Observational Studies in Epidemiology using Mendelian Randomization.